Content Creator Legal Protection of The Copyrights of Content Reuploaded by Other Parties for Commercial Purposes - Fayola, Carissa; Sitompul, Roswita; Isnainul, OK (IJBLE Scientific Publications Community Inc., 2024)
In the current era of globalization, technological advancements are rapidly progressing, especially in the field of information technology, giving rise to the phenomenon of